Impact of Human Resource Management Practices on Organizational citizenship Behavior: an Empirical investigation from Banking Sector of Sudan - Abdallah Ahmed, Nazar Omer (International Review of Management and Marketing, 2016)
The study is specifically aimed to explore individual and joint effect of human resource management (HRM) practices on organizational citizenship behaviour (OCB) among Sudanese banking staff Questionnaires were distributed to 298 respondents to three banks called Sudanese French Bank, Saudi Sudanese Bank and National Bank of Abu Dhabi. Pearson Correlation analysis was used to investigate the relationship between various HRM practices and OCB while Multiple Regression analysis was used to find out the joint effect of various HRM practices against OCB. It was found that all HRM practices used in this study have positive effects on OCB. Some practices have a weaker effect in comparison to other practices against OCB whereas some practices show a strong correlation with OCB. Overall, the results of this research have been discussed and the recommendations for organizations have been suggested at the end of the study. Keywords: Human Resource management practices, organization citizenship behavior, Sudan, Banking Sector JEL Classifications: M1, M10, M19